Lermontov’s religious and ethical ideal: sources of formation and artistic realization - Киселёва, Ирина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
Ethics by Lermontov are deeply original and have a religious character. According to Christian canons, in the poet’s consciousness, the source of moral is acting and a measure of a moral sense is Christ. Primary in Lermontov’s poetry is the accusation of his generation’s flaws. Also acusation of defectsc are strong in his creativity. The leading motive of Lermontov’s poetry is that of God's court, which acts as a justice standard.